2015
DOI: 10.5430/jha.v5n1p52
|View full text |Cite
|
Sign up to set email alerts
|

The storied mind: A meta-narrative review exploring the capacity of stories to foster humanism in health care

Abstract: Objective: Healthcare organizations are increasingly engaging the voice of patients and families through storytelling initiatives in hopes that this will yield compassionate and humanistic outcomes. To date, very little research is available that directly guides and justifies storytelling initiatives as a mechanism for promoting humanistic culture shifts in healthcare. This review aimed to uncover diverse research and evidence on how storytelling can be utilized to promote humanistic shifts in healthcare organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…The power of storytelling for enhancing understanding and emphasizing the humanness of specific situations has been consistently described in the literature in relation to education (Hall & Powell 2011;Gidman 2013) and healthcare (Rose et al 2015). More specifically, in mental health, storytelling is described as bringing humanity to the experiences of people diagnosed with mental illness and enhancing students' capacity to understand those experiences from a personal and human perspective (Grant et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The power of storytelling for enhancing understanding and emphasizing the humanness of specific situations has been consistently described in the literature in relation to education (Hall & Powell 2011;Gidman 2013) and healthcare (Rose et al 2015). More specifically, in mental health, storytelling is described as bringing humanity to the experiences of people diagnosed with mental illness and enhancing students' capacity to understand those experiences from a personal and human perspective (Grant et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A significant aspect of a narrative review is that it makes explicit search criteria and inclusion criteria (Green, Johnson, Claire, & Adams, 2006). Study I sought to unveil the patterns and/or significant themes discussed by the extant literature on the subject (Rose et al, 2016). The ambition was to reveal existing themes found within the contemporary academic discourse and to what degree these themes were supported by the unearthed articles, and thereby garner an understanding for what theme was the most prevalent in the ongoing academic debate on the subject (Cronin, Ryan, & Coughlan, 2008;Penrose & Katz, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Second, an objectivist epistemology is inherently suspicious of an individual's objective memory recall (Crotty, 1998), which shifts the focus away from finding meaningful lessons in a story to a preoccupation with confirming if the events "actually" occurred in the way they were described. Finally, health care research and practice often has a homogenous, ethical framework in which blinded studies and fully de-identified data are the gold standard (Rodgers, 2005). Therefore, participants using their own voices and photos in a DS could be viewed as an ethical breach of confidentiality.…”
Section: Limitations Of Dst In a Health Care Contextmentioning
confidence: 99%
“…Health care, like many sectors, is currently experiencing a storytelling renaissance (Rose, Mason-Lai, Brocke, Page, & Cawthorpe, 2016). This is facilitated in part by the convergence of influential ideas of narrative medicine (Charon, 2001;Holmgrem, Fuks, Boudreau, Sparks, & Kreiswirth, 2011), reflective practice (Schön, 1983(Schön, , 1987, patient engagement (Carman et al, 2013;National Academies of Science [NAS], 2011), person-centered care (NAS, 2001), participatory action research (Koch & Kralick, 2006), and the emerging discipline of the health humanities (Crawford, Brown, Baker, Tischler, & Abrams, 2015).…”
Section: Introductionmentioning
confidence: 99%